Carbon, nitrogen and granulometric fractions in biogenic and physiogenic aggregates of a soil with a history of 10-years of successive swine waste applications (Research, Society and Development, 2020)
The objective of this study was to evaluate the effects of the use of different sources and quantities of waste on the total carbon (C) and nitrogen (N) contents and the particle size fractions of organic matter (OM) the soil biogenic and physiogenic aggregates. Soil samples were collected at depths 0-5cm and 5-10cm, in the treatments without application of manure (Control), with application of pig slurry (PS) and deep litter (DL) at equivalent doses you once and twice recommended N for corn and oats (PS1X, PS2X, DL1X and DL2X, respectively). The aggregates were separated according to the formation pathway (biogenic and physiogenic). Subsequently, total C and N, and OM fractions were quantified. The application of CSS increased the total C and N contents of aggregates and OM fractions. The application of swine manure increased the C and N in biogenic aggregates compared to the physiogenic ones.